Diritto alla casa e Statuto Urbano: nuove metodologie per la regolarizzazione di aree marginali in Brasile - DOI: 10.5752/P.2316-1752.2009v16n18/19p295 - Mingucci, Roberto; Muzzarelli, Aurelio (Cadernos de Arquitetura e Urbanismo, 2010)
Abstract This paper refers to an urban land regularization project (collective adverse possession) developed in order to apply Law “ Estatuto da Cidade 10.257/01, 10 de julho de 2001” (“City Statute 10257/01, as of July 10, 2001”), based on the right to housing as a social right established by the Brazilian Federal Constitution. Its main contribution consists of the experimentation of some potentialities and a critical view of the use of geographic information and communication technologies applied to that kind of process, which requires cartographic representation of urban areas involved in land regularization actions. Key words : Urban land regularization; Cartographic representation; GIS; WebGIS.